480 PULMONARY FUNCTION DATA USED TO DETERMINE ASBESTOSIS IMPAIRMENT MAY BE FLAWED - Jensen, R. L.; Crapo, R. O.; Howell, H. M (Journal of investigative medicine, 2005)
More than 200,000 personal injury cases alleging nonmalignant asbestosis are now pending, many of them based on medical data from screening entities set up under contract with plaintiff attorneys. In addition, more than 50,000 new cases are being filed every year. We evaluated a random sample of 272 pulmonary function reports submitted by one such screening entity for litigation. Demographic, spirometry, lung volume and diffusing capacity (DLCO) data from each chart were entered into a database using a single-entry system with an entry error rate of less than 1%. The sample included 228 men and 36 women with an average age of 62.3 + 8.8 years. We reviewed the tests for adequacy, choice of reported values and internal consistency. Forced expiratory capacity (FVC) was analyzed. More than 8% (8.1%) of the FVCs reported were lower than other FVC values measured at the same time. Inspiratory vital capacities were larger than reported FVC 15.4% of the time. Compared to other measures of vital capacity found in the same medical chart, 50.4% reported an FVC lower than the vital capacity. Differences between the largest and the next largest vital capacity were more than 400 ml in 22.1%; in 8.8% the difference was more than 1000 ml. Had percent predicted values (without adjusting for ethnic values) been based on the largest vital capacity, 14.3% of the subjects would have been classified as normal. Lung volumes were measured by the nitrogen washout method, a method requiring quiet slow breathing during the procedure. In our sample, 45.8% had breathing frequencies ≥30 breaths per minute; 6.3% ≥ 60 breaths per minute. Residual volume was more than half the total lung capacity in 21.7% of the subjects. DLCO was measured within minutes of the nitrogen washout test. In 64.1% of the tests where the technician adjusted the alveolar sample volumes, the sample contained significant qualities of dead space gas. The equipment used to test DLCO reported errors when the procedure was not done correctly; 23.2% of the reports we reviewed showed machine-generated error reports. As a group, these tests do not meet ATS standards. There are test quality problems in every major category of pulmonary function testing for this sample of pulmonary function tests suggesting the tests are not acceptable to determine the presence or absence of impairment.